Understanding the motivations and fears towards COVID-19 pandemic duty among undergraduate medical students of largest city in Gujarat. (Indian Journal of Public Health Research & Development, 2025)
Background: COVID-19, which began in Wuhan in December 2019 and became a global pandemic by March 2020, severely strained healthcare systems. In response, the Indian government deployed medical students as COVID-19 assistants to address the healthcare worker shortage. In Gujarat, 5,500 students from various colleges were trained and assigned to public health facilities during the pandemic's waves. This study investigates the motivations and fears of these students to guide future public health emergency protocols.Methods: This descriptive cross-sectional study was conducted among 1,660 medical students from five medical colleges of Ahmedabad city who participated in COVID-19 duties. Using a pretested questionnaire, data on students' fears and motivations were collected. Statistical analyses were performed with IBM-SPSS, employing descriptive statistics and independent t-tests, with significance set at p
Keywords: COVID-19 pandemic; Fears; Motivations; Medical students